Features of passivation, oxidation and combustion of tungsten nanopowders by air; International Journal of Refractory Metals and Hard Materials; Vol. 22, № 6 - Kwon Y. S.; Gromov A. A. Aleksandr Aleksandrovich; Ilyin A. P. Aleksandr Petrovich; Ditts A. A. Aleksander Andreevich; Kim J. S.; Park S. H.; Hong M. H. (2004, 2004)
Title screen